南極ドームふじ基地における第2期氷床深層コア掘削 - 本山, 秀明; モトヤマ, ヒデアキ; 高橋, 昭好; タカハシ, アキヨシ; 田中, 洋一; タナカ, ヨウイチ; 新堀, 邦夫; シンボリ, クニオ; 宮原, 盛厚; ミヤハラ, モリヒロ; 吉本, 隆安; ヨシモト, タカヤス; et al. (国立極地研究所, 2020)
南極ドームふじ基地において，第2 期氷床深層コア掘削が行われた．2001 年のパイロット孔掘削に引き続き2003/2004 シーズンから4 か年にわたり本格的な深層コア掘削を実施し，2007 年1 月に3035.22 m 深に達した．夏期間のみの掘削としたので，効率よく掘削できるように第1 期深層コア掘削システムの問題点を解決しながら多くの改良を施した．特に1 回の掘削で採取可能なコア長を2.3 m から3.84 m にしたことと切削チップ収納効率を高めたことが大きい．本報告では，現地で使用した掘削システムの概要とともに，掘削の方法，掘削の経過を述べるとともに，掘削中に生じた様々なトラブルについても報告し，併せて今後の課題を示した． The second deep ice coring project was carried out at Dome Fuji, Antarctica. Following the pilot hole drilling in 2001, deep ice core drilling was conducted for four years from the 2003/2004 austral summer season, reaching a depth of 3035.22 m in January 2007. The drilling was performed only in the summer season. Therefore, many improvements were made to the problems of the first deep ice core drilling system to enable efficient drilling. In particular, the core length that can be obtained at one time was increased from 2.3m to 3.84 m, and the chip storage efficiency was enhanced. In this report, the outline of the drilling system, the method of drilling, the progress of drilling operation, and various troubles were reported. Also, future issues are indicated. departmental bulletin paper